The Effect of Different Combinations of Pedal Rate and Load during Ergometer Cycling at Different Work Rates on the Muscle Activities of the Lower Limbs - KONISHI, Yuto; YOSHIDA, Masaki; IWASHITA, Atsushi (Rigaku ryoho kagaku, 2013)
[Purpose] To measure muscle activities at different pedal rates and work loads during ergometer cycling at work rates of 60, 120, and 180 W, and determine their average and maximum values. [Subjects] The subjects were 10 healthy adults. [Method] Electromyographic activities of the rectus femoris, vastus medialis, vastus lateralis, semimembranosus, gastrocnemius, and tibialis anterior were measured. [Results] At 60 and 120 W, the average muscle activities showed high values at low work loads with fast pedal rates, and showed low values at moderate work load and pedal rate at 180 W. For the maximum value, all of the muscles, except the semimembranosus, showed high values at low load with fast pedal rate at 60 W. At the higher work rates of 120 and 180 W, maximum muscle activities showed low values at moderate load and pedal rate, and high values at high load and low pedal rate. [Conclusion] At each work rate, there is a work load and pedal rate combination that will achieve endurance training with suppressed muscle activity and high exercise efficiency, as well as one that will raise muscle activity for muscle strengthening, and the results suggest consideration needs to be given to this during training.